THE EFFECT OF INVESTMENTS AND GOVERNMENT EXPENDITURE TOWARDS ECONOMIC GROWTH OF DISTRICTS/CITIES IN WEST JAVA 2016 - 2020 - Zuffar Ikhsan Pratama; Pratama, Aditya; Sariwulan, Rd. Tuty (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study aims to determine the effect of investment and government expenditure on the economic growth of districts/cities in the province of West Java. Data obtained indirectly obtained by researchers through other parties. Data in the form of annual investment and government spending, as well as Gross Regional Domestic Product (GRDP), were collected from 2015 to 2020 and covered 12 districts/cities in West Java. The data analysis method used in this study is multiple linear regression using SPSS software. The results show that there is a positive and significant effect of investment on economic growth, there is a negative and significant effect of government spending on economic growth, there is a simultaneous effect of investment and government spending on economic growth.